{The gersdorffite-bismuthinite-native gold association and the Skarn-Porphyry mineralization in the Kamariza Mining district, Lavrion, Greece} - Voudouris, Panagiotis; Mavrogonatos, Constantinos; Rieck, Branko; Kolitsch, Uwe; Spry, Paul G.; Scheffer, Christophe; Tarantola, Alexandre; Vanderhaeghe, Olivier; Galanos, Emmanouil; Melfos, Vasilios; Zaimis, Stefanos; Soukis, Konstantinos; et al. (Minerals, 2018)
Vein-type Pb-Ni-Bi-Au-Ag mineralization at the Clemence deposit in the Kamariza and “km3” in the Lavrion area, was synchronous with the intrusion of a Miocene granodiorite body and related felsic and mafic dikes and sills within marbles and schists in the footwall of (and within) the Western Cycladic detachment system. In the Serpieri deposit (Kamariza area), a porphyry-style pyrrhotite-arsenopyrite mineralized microgranitic dike is genetically related to a garnet-wollastonite bearing skarn characterized by a similar base metal and Ni (up to 219 ppm) enrichment. The Ni–Bi–Au association in the Clemence deposit consists of initial deposition of pyrite and arsenopyrite followed by an intergrowth of native gold-bismuthinite and oscillatory zoned gersdorffite. The zoning is related to variable As, Ni, and Fe contents, indicating fluctuations of arsenic and sulfur fugacity in the hydrothermal fluid. A late evolution towards higher sulfur fugacity in the mineralization is evident by the deposition of chalcopyrite, tennantite, enargite, and galena rimming gersdorffite. At the “km3” locality, Ni sulfides and sulfarsenides, vaesite, millerite, ullmannite, and polydymite, are enclosed in gersdorffite and/or galena. The gersdorffite is homogenous and contains less Fe (up to 2 wt.%) than that from the Clemence deposit (up to 9 wt.%). Bulk ore analyses of the Clemence ore reveal Au and Ag grades both exceeding 100 g/t, Pb and Zn > 1 wt.%, Ni up to 9700 ppm, Co up to 118 ppm, Sn > 100 ppm, and Bi > 2000 ppm. The “km3” mineralization is enriched in Mo (up to 36 ppm), Ni (>1 wt.%), and Co (up to 1290 ppm). Our data further support a magmatic contribution to the ore-forming fluids, although remobilization and leaching of metals from previous mineralization and/or host rocks, through the late involvement of non-magmatic fluid in the ore system, cannot be excluded.
Keywords: Bismuth; Gold; Greece; Lavrion; Nickel sulfides-sulfarsenides; Oscillatory zoning